СHANGES OF IMMUNOREGULATORY INDEXES IN CHILDREN EXPOSED TO STRONTIUM - E. A. Otavina (SPb RAACI, 2018)
Evaluation of the immune system parameters can be used in order to assess capacity to adapt under conditions of increased external chemical load, including exposure to metals, which can exert either activating and inhibitory effects upon immune regulation parameters. The aim of this work was the analysis of immunoregulatory markers in a children’s population who consumed water with high strontium content (a sample from the Perm region). We carried out immunological evaluation of the children aged 7 to 12 years, living at a territory with a high strontium content in the drinking water. The comparison group included children from the conventionally clean region. We studied differential changes in cellular immunity (phagocytosis rates), humoral factors of immune defense (serum immunoglobulins), development of specific sensitization for strontium, as well as the processes of apoptosis triggering and regulation. A 3.68-fold increase in strontium levels was shown in fresh water within observation area, and the average  blood strontium content in the children of appropriate observation group was 1.55-fold higher than in children of the comparison group. At the same time, 1.2-fold increase in phagocytic activity determined as phagocytic number and phagocytic index was found, as compared to the control group. In 80% of the subjects, a reduction in serum IgG level was observed when compared to physiological norm, as well as a significant decrease in IgG and enhance in IgM production against the levels found in the comparison group. Wehave also shown an enhanced total sensitization in 55.0% of the observation group as shown by the total IgE test compared with normal age ranges, as well as excessive specific sensitization to strontium by 2.49 times, according to the IgG criterion. Disturbance in apoptosis triggering was associated with decreased number of CD95+ lymphocytes and TNFR1+ cells (2.8-fold compared to reference values), shifted balance in apoptogenic proteins, an average of 2.6-fold decrease in Bcl-2 expression, a 2.8-fold reduction of the p53 transcription factor expression relative to the reference interval. Thus, we have shown an ability of strontium excess in drinking water to influence the most important indices of immune regulation in pediatric population. These changes may serve as indices of populational health status under of external strontium exposure.